Characterization of a novel scale maille contralateral breast shield: SMART Armor. (11th August 2017) - Butson, Macinley; Carroll, Susan; Butson, Martin; Hill, Robin
Abstract: During breast radiotherapy treatment, the contralateral breast receives radiation doses to the skin and subcutaneous tissue caused mainly from incident electron contamination and low energy photon scatter radiation. Measurements have shown that for a typical hybrid tangential treatment, these dose levels can be up to 17% of maximum applied prescription dose if no shielding is used during the treatment process. This work examined the use of different shielding metals, aluminum, copper, and lead to reduce peripheral radiation dose to evaluate the optimal metal to form the basis of a contralateral breast radiation shield. This work also shows a simple but novel method to substantially reduce this unwanted radiation dose with the use of a copper scale maille sheet which can be easily and accurately draped over a patient's contralateral breast during treatment. The copper scale maille is flexible and can thus conform around typical breast shapes. It can also form irregular shaped edges to match those outlined by typical tangential treatment fields. As the shield is made from copper, it is nontoxic and can potentially be used directly on patients for treatment. The designed copper scale maille has shown to reduce contralateral breast skin and subcutaneous dose by up to 80% for typical radiation fields used in breast radiotherapy.